Crop productivity and tree growth in intercropped agroforestry systems in semi-arid and sub-humid regions of Ethiopia - Tadesse, S.; Gebretsadik, W.; Muthuri, Catherine W.; Derero, A.; Hadgu, K.; Said, H.; Dilla, A. (Springer, 2021)
Agroforestry has been practiced traditionally by smallholder farmers in tropical countries, including Ethiopia. However, scientific information on tree-crop interactions isn’t widely available. Long-term agroforestry field experiments were conducted, in sub-humid and semi-arid regions of Ethiopia, to explore the impacts of intercropping on crop yield and tree growth. The treatments in the sub-humid areas were; tree alone (Cordia, Grevillea, Croton, and Acacia abyssinica), (2) crop alone, teff (Eragrostis tef), maize (Zea mays) and finger millet (Eleusine coracana), (3) tree + crop, (4) mix of four tree species and (5) mix of tree species + crops. The treatments in the semi-arid area included (1) tree + crop (teff with Faidherbia, Moringa, Acacia nilotica and Cordia, (2) crop alone, and (3) mix of trees + crops. The species choice was determined by suitability to local contexts and from farmer prioritisation participatory design workshops. Crop yield, tree height, and diameter were measured from each treatment. Crop yields under tree + crop treatments were not significantly different (α = 0.05) from crop yield in the sole crop treatments (in both areas), except crop yields under Acacia abyssinia, which had the lowest crop yields compared to the rest of the treatments in the sub-humid areas. In the semi-arid area, teff yield under Faidherbia in 2019, has increased by 64%, compared to the yield in 2017. The best growth performance was attained by Grevillea and Cordia in the sub-humid areas, whereas Acacia nilotica performed well in the semi-arid areas. These results suggest that the selection of appropriate tree and crop species can enhances crop and tree production in agroforestry systems of Ethiopia.